Commercial determinants of health: future directions. Issue 10383 (8th April 2023) - Friel, Sharon; Collin, Jeff; Daube, Mike; Depoux, Anneliese; Freudenberg, Nicholas; Gilmore, Anna B; Johns, Paula; Laar, Amos; Marten, Robert; McKee, Martin; Mialon, Melissa
Summary: This paper is about the future role of the commercial sector in global health and health equity. The discussion is not about the overthrow of capitalism nor a full-throated embrace of corporate partnerships. No single solution can eradicate the harms from the commercial determinants of health—the business models, practices, and products of market actors that damage health equity and human and planetary health and wellbeing. But evidence shows that progressive economic models, international frameworks, government regulation, compliance mechanisms for commercial entities, regenerative business types and models that incorporate health, social, and environmental goals, and strategic civil society mobilisation together offer possibilities of systemic, transformative change, reduce those harms arising from commercial forces, and foster human and planetary wellbeing. In our view, the most basic public health question is not whether the world has the resources or will to take such actions, but whether humanity can survive if society fails to make this effort.